Attachment and Marital Adjustment: Mediating Roles of Emotion Regulation and Rejection Sensitivity - Temiz, Zahide Tepeli; Bilican, F. Işıl (Wiley, 2023)
Attachment styles have important effects in shaping and maintaining the adjustment between couples. The development of emotion regulation skills and sensitivity to rejection in interpersonal relationships are explained within the framework of attachment theory. This study aims to examine the relationship between romantic attachment patterns, emotion regulation, rejection sensitivity and marital adjustment. Also, the mediating effects of rejection sensitivity and emotion regulation will be examined. The sample consists of 346 married individuals living in the city of Istanbul (Nfemale =173, Mage =39.78; Nmale =173, Mage =43.19). The findings of the regression analysis show that the anxiety and avoidance dimensions of romantic attachment negatively predict marital adjustment and relationship satisfaction. In multiple regression analyzes, it was found that the sensitivity to rejection and difficulty in emotion regulation negatively affected the marital adjustment. In addition, while only the anxiety dimension of insecure attachment predicts emotion regulation difficulty, both anxious and avoidant attachment patterns affect rejection sensitivity. The findings of the mediation analysis show that the increase in attachment anxiety amplifies the difficulty in emotion regulation and this decreases the adjustment between the couples. Difficulty in emotion regulation fully mediates the relationship between anxious attachment pattern and marital adjustment. In summary, the findings of the study support the attachment theory and show that early structures continue to affect romantic relationships in adulthood. Based on the findings, therapeutic interventions to regulate emotions are expected to contribute positively to both attachment patterns and the relationship quality of married couples.